Pembangkit listrik tenaga biogas di Desa Monapa Kabupaten Kowane Selatan - Mansur Mansur; Muhammad Muhammad; Luther Luther (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Electricity needs are still dependent on electricity supply from PT. PLN and the cost are very expensive for people in rural areas so that it is necessary to look for other alternative energy that is easy to obtain and environmentally friendly namely energy derived from biogas by building a biogas power plant where biogas is produced by biogester. Biogas is a substitute for fuel oil, to run a generator to produce electricity. The electricity produced can be used as a source of electrical energy in rural communities. The use of electricity from biogas power plants is used for household electricity needs and the use of machine tools for fruit processing used in UMKN (Micro, Small and Medium Enterprises).